Penerapan Konsep Geometri Transformasi Terhadap Perancangan Desain Piagam Penghargaan Pegawai BPKP Perwakilan Aceh - Maysarah, Siti; Yuni, Syarifah Meurah; Zuhra, Rahma; Irawati, Cut (Jurnal Riset dan Pengabdian Masyarakat, 2024)
Design or designing is a process of planning and creating a new object which is carried out by taking into account various aspects which include beauty, symmetry, and aesthetics as well as various other aspects. The design process can also be referred to as visual problem solving which includes organizing, creating, and evaluating to produce the desired work. An award charter is a media that contains writing in the form of an official statement and is used as a form of appreciation for one's achievements or accomplishments. The award certificate is created through the design process first, where all ideas are conveyed through the creation of objects in the design. In designing the charter design, the concept of transformation geometry can be applied to get changes in location and presentation based on several types of transformations, so that later a design will be produced according to the needs and desires. The types of transformation geometry that will be used include translation, rotation, reflection, and dilation. The concept of this transformation geometry is used in the design and determination of the charter design to be given to BPKP Aceh Representative employees who excel.